2013
DOI: 10.1186/1129-2377-14-30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of primary headache disorders among a local community in Addis Ababa, Ethiopia

Abstract: Background: Headache disorders are the most common complaints worldwide. Migraine, tension type and cluster headaches account for majority of primary headaches and improvise a substantial burden on the individual, family or society at large. There is a scanty data on the prevalence of primary headaches in sub-Saharan Africa in general and Ethiopia in particular. Moreover there is no population based urban study in Ethiopia. The purpose of this study is to determine the prevalence and burden of primary headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 31 publications
7
41
5
1
Order By: Relevance
“…We can compare our results in workers with two studies among workers of a textile factory in Ethiopia (35). The one-year prevalence of migraine was 6.2% and of TTH 9%, almost the same as in workers in our study (7.3%), but the prevalence of TTH was significantly lower than in our study (37%).…”
Section: Headache Prevalence Differs Among Social Groupssupporting
confidence: 71%
“…We can compare our results in workers with two studies among workers of a textile factory in Ethiopia (35). The one-year prevalence of migraine was 6.2% and of TTH 9%, almost the same as in workers in our study (7.3%), but the prevalence of TTH was significantly lower than in our study (37%).…”
Section: Headache Prevalence Differs Among Social Groupssupporting
confidence: 71%
“…The prevalence of migraine reported in this study both overall and by sex is consistent with results of 2 previous population‐based US prevalence studies, the AMS I and AMS II demonstrating that the roughly three‐to‐one female to male sex PR has remained relatively stable in the United States over the past 30 years. Although rates vary to some degree from reports both within the United States and from other countries,1,3‐30 the female preponderance in migraine is consistent. Variations in prevalence may be due to true differences in prevalence or differences in methodology and sampling strategy.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to the female preponderance in migraine prevalence, some studies have reported that females may experience greater symptomology and headache‐related disability . Sex differences have also been observed in the prevalence of probable migraine (PM), although the direction is not always consistent . Few data are available on sex differences in associated symptomology, frequency, and disability in PM.…”
mentioning
confidence: 99%
“…A higher prevalence was recorded in Zambia (72%) (gender- and habitation-adjusted 61.6%) [34] whereas, lower prevalence was reported in Ethiopia (21.6%) [35] and Tanzania (23.1%) [36]. The differences in the prevalence could be attributed to different methodologies used, as well as cultural and population characteristics of the studied patients.…”
Section: Discussionmentioning
confidence: 98%